2013
DOI: 10.1080/15438627.2013.792089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low Volume Injury Prevention Program on the Hamstring Torque Angle Relationship

Abstract: The effects of a 4-week lower body injury prevention program on knee muscle torque-angle relationship were examined in soccer players. Twenty men were randomly allocated to either a control (n = 10) or training group (n = 10). The training group underwent three training sessions per week, comprising 3 sets of 8 repetitions of one open-chain exercise (Nordic curl) and two closed-chain exercises-forward lunges on a Bosu balance trainer and eccentric single leg dead lifts. Maximal peak knee flexion torque was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 21 publications
0
46
0
1
Order By: Relevance
“…Different eccentric exercises using a fly wheel eccentric leg curl 19 , Nordic Curl alone 8,20 combined with other strengthening 21 or stretching exercises 21,22 have been successfully applied for reducing the incidence of hamstring injuries, enhancing hamstring eccentric strength 23 or shifting the optimal peak torque in non-previous injured a thletes [24][25][26] . However, the loading patterns and the appropriate training protocols continue to be determined.…”
Section: Active Lengthening Exercisesmentioning
confidence: 99%
See 4 more Smart Citations
“…Different eccentric exercises using a fly wheel eccentric leg curl 19 , Nordic Curl alone 8,20 combined with other strengthening 21 or stretching exercises 21,22 have been successfully applied for reducing the incidence of hamstring injuries, enhancing hamstring eccentric strength 23 or shifting the optimal peak torque in non-previous injured a thletes [24][25][26] . However, the loading patterns and the appropriate training protocols continue to be determined.…”
Section: Active Lengthening Exercisesmentioning
confidence: 99%
“…In addition, to the active lengthening observed during sprints or kicking, the hamstring acts as knee stabilisers counteracting and balancing the actions of the quadriceps during sportspecific activities, such as landing, deceleration or change of direction. Therefore, specific drills involving, repeated sprints, jumps, hops combined with unstable coreexercises, namely one-leg squat or lunges unstable surfaces have been proposed as effective methods for preventing hamstring injuries 24,27,28 . Verral et al 28 reported a significant reduction of hamstring injuries in Australian football players after a four-year high-intensity intervaltraining programme combined with passive isometric hamstring stretching.…”
Section: Unstable-core and Sport Specific Exercisesmentioning
confidence: 99%
See 3 more Smart Citations